Prosthechea ionophlebia and P. chacaoensis two different species, but which is which? - Pupulin, Franco (2007)
Prosthechea ionophlebia and P. chacaoensis can be distinguished using several characters. Based on classical literature, the only diagnostic differences between P. chacaoensis and P. ionophlebia are flower size and the shape of the lip. However, the study of living specimens grown at Lankester Botanical Garden, University of Costa Rica, revealed consistent differences between the two taxa in their lip length/width ratio, disc, venation and margins. Differences are also seen in capsule morphology and vegetative features, even though the latter might be influenced by environmental factors.